880 Drive in drive out coal miners: an accident waiting to happen. (1st September 2016) - Davey, Jeremy; Potter, Candice; Armstrong, Kerry
Abstract : Background: Australian mining sites and cover vast areas of the country are often located hundreds of kilometres from major centres. Thousands of mine workers reside in major population centres in coastal communities and regularly drive hundreds of kilometres to and from their workplaces at remote mine sites. This exposes many workers particularly on completion of their working week to the behaviours of high-risk fatigue and remote area driving. Methods: Data was collected using in-depth interviews ( n = 37) and a written survey ( n = 461) of employees from a Queensland coal mine. As well as collecting demographic and behaviour data the survey also contained constructs on the theory of planned behaviour, to examine the workers decisions about driving immediately after their rosters of 12 to 14 hrs. shifts over seven to ten day periods. Results: Workers drove an average of 473 km at the end of their rosters and almost one third drove over 600 km. There was an overwhelming desire to leave site as soon as possible after rosters. This desire frequently overrides concerns about high risks associated with fatigue and remote area driving. Facilitating factors include routine, sick of being on site, to get the drive over with, and because workers perceive they are experienced drivers . There were notable variations between factors that facilitate leaving site immediately. These variations and different control beliefs are predominately due to the type of shift (i.e. day or night). Conclusions: This research identified that many workers could be driving after being awake for up to 20 hours on the last day of shift. This level of wakefulness can impair driving that is equivalent to a BAC of 0.10%. The current study is understood to be the first to provide insight into the factors that facilitate and act as a barrier to mine workers driving immediately following their shift blocks. Interventions need to consider different shift types and the variations in intention and behaviour of worker commuting.